Human fetal and maternal corticotrophin releasing hormone responses to acute stress. Issue 1 (1st January 2004) - Gitau, R; Fisk, N M; Glover, V
Abstract : Objectives: To study the effect of acute stress, caused by intrauterine needling at the intrahepatic vein (IHV), on fetal plasma concentrations of corticotrophin releasing hormone (CRH), and to compare paired fetal and maternal samples for CRH concentration to determine the extent of their joint control. Design: Venous blood samples were obtained from fetuses (gestational age 17–38 weeks) undergoing fetal blood sampling (n = 29) or intrauterine transfusion (n = 17) through either the IHV or the placental cord insertion (PCI). Setting: The Centre for Fetal Care, Queen Charlotte's and Chelsea Hospital, London, UK. Patients: Pregnant women undergoing clinically indicated fetal blood sampling or intrauterine blood/platelet transfusion. Results: Fetal plasma cortisol increased with intrahepatic vein transfusion (mean (SD) cortisol response Δ64.7 (54.5) nmol/l; p < 0.0001, n = 11), and fetal corticotrophin concentrations were higher after IHV (n = 7) than PCI needling (n = 6). Neither fetal nor maternal plasma CRH increased after IHV transfusion. Fetal CRH levels did not rise with gestation, whereas maternal CRH levels did ( r = 0.58; n = 36; p < 0.0001). There was a modest correlation between paired maternal and fetal values ( r = 0.36; n = 36; p = 0.03). Conclusions: Acute fetal stress, caused by IHV needling of the fetal abdomen, resulted in hypothalamic-pituitary-adrenal axis activation, as shown by a rise in fetal cortisol and corticotrophin. However, it did not result in measurable CRH release into fetal plasma. This suggests that fetal plasma CRH is not derived from the hypophyseal-portal circulation, but from another source, presumably the placenta.